Project management success factors: in research of product development project specialities - Soltész, László; Kamondi, László; Berényi, László (Design of Machines and Structures, 2020)
Project success is a multifactorial issue, including difficult to quantify, soft factors as well. Project management style, collaboration within the team, and the level of standardisation may have an essential influence on the deliverables, moreover, on corporate performance. A prescription answer is not achievable considering the individual characteristics of projects but finding best practices and critical factors help to improve the performance. This paper presents the results of a survey among product development project experts (n = 112) evaluating the relevance of some success factors and their practical experience in the field. The results show that keeping the project plan and managing long-term issues like lessons learned database or module database are the most critical factors of success. The analysis did not find patterns of the responses that confirms the need for unique management actions.